Silencers in Flow Ducts using Double-Layer MPA - Berchtenbreiter, Benedikt; Grützner, Dominik; Czwielong, Felix; Becker, Stefan (30th AIAA/CEAS Aeroacoustics Conference, 2024, 2024)
Microperforated absorbers (MPA) are an established technology for the attenuation of sound in flow-carrying ducts. MPAs usually consist of a microperforated panel (MPP) in combination with a back volume. The damping maxima of MPAs occur in the range of their resonant frequencies and the effect is narrowband compared to passive porous or fibrous absorbers, which damp broadband at high frequencies. The resonant frequencies of MPAs decrease with increasing back volume. To reduce the required back volume, a double-layer MPAs with an additively manufactured porous absorber underneath the MPP as an acoustic metamaterial are introduced. The advantage of using additively manufactured absorbers over conventional absorbers is that the acoustic properties can be specifically adapted to the required impedance boundary conditions. The reflection, transmission and dissipation of the investigated mesh structures correspond to the characteristics of porous absorbers. The effective fluid properties of the individual grating structures were successfully determined using the admittance matrix of the structures. With the possibility of modelling the grids as an effective fluid, a design of the double-layer MPA was obtained. The results show that the additively manufactured absorbers reduce the required back volume by up to 13% in comparison to a single layer version. Finally, measurements were carried out with channel flow at Mach numbers up to 0.1. The sound-attenuating effects of both single-and double-layer MPAs were changed in the frequency and amplitude depending on the flow velocity parameters.
CRIS-Team Scopus Importer:2024-09-06